2015
DOI: 10.1161/strokeaha.115.009589
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Blood–Brain Barrier Permeability Changes in Binswanger Disease

Abstract: Background and Purpose The blood brain-barrier (BBB) is disrupted in small vessel disease (SVD) patients with lacunes and white matter hyperintensities (WMHs). The relationship of WMHs and regional BBB permeability changes has not been studied. We hypothesized that BBB disruption occurs in normal appearing WM (NAWM) and regions near the WMHs. To test the hypothesis, we repeated BBB permeability measurements in patients with extensive WMHs related to Binswanger’s disease (BD). Methods We selected a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 24 publications
7
115
1
1
Order By: Relevance
“…25 26 Recently, a study among patients with Binswanger disease demonstrated that abnormal WM permeability (WMP) was more frequently detected in NAWM than in WMHs, with the highest frequency in a 4 mm width ring surrounding the WMHs, which coincided with the aforementioned finding that the surrounding NAWM was vulnerable, leading to progression of WMHs. 27 Histopathological and postmortem imaging findings in NAWM Autopsy studies confirmed that the underlying pathological changes of LA extended into the NAWM. Among six AD patients with LA, neuropathological examination revealed much more extensive changes in WM than did parallel postmortem MRI, with a mean of 54% larger abnormal areas.…”
Section: Disruption Of Microstructures In Nawmmentioning
confidence: 84%
“…25 26 Recently, a study among patients with Binswanger disease demonstrated that abnormal WM permeability (WMP) was more frequently detected in NAWM than in WMHs, with the highest frequency in a 4 mm width ring surrounding the WMHs, which coincided with the aforementioned finding that the surrounding NAWM was vulnerable, leading to progression of WMHs. 27 Histopathological and postmortem imaging findings in NAWM Autopsy studies confirmed that the underlying pathological changes of LA extended into the NAWM. Among six AD patients with LA, neuropathological examination revealed much more extensive changes in WM than did parallel postmortem MRI, with a mean of 54% larger abnormal areas.…”
Section: Disruption Of Microstructures In Nawmmentioning
confidence: 84%
“…Diffusion tensor imaging provides another indicator of structural damage to white matter [58]. Finally, DCEMRI is a functional measure of the leakiness of blood vessels, which indicates the presence of neuroinflammation [59, 60]. The combination of multiple modalities provides a clear picture of the extent of damage and the possible etiology of the injury in white matter.…”
Section: Methodsmentioning
confidence: 99%
“…4,[17][18][19][20][21][22][23][24] Recent work has also identified changes in permeability in NAWM following whole brain radiotherapy in patients with cerebral tumors. 25 The increase in BBB permeability induced by whole-brain radiotherapy has been used to improve penetration of therapeutic agents for the treatment of primary central nervous system (CNS) lymphoma and metastatic disease typically depending on simultaneous measurement of cerebrospinal fluid (CSF) and plasma concentrations of the therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%